2015
DOI: 10.2471/blt.14.139527
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in the perceived quality of primary care in Shanghai and Shenzhen, China: a difference-in-difference analysis

Abstract: ObjectiveTo assess changes in the quality of primary care in two megacities following the introduction of health system reforms in China.MethodsWe conducted multistage stratified random face-to-face surveys of patients visiting community health centres in Shanghai in 2011 and 2013, and Shenzhen in 2012 and 2013. Quality of primary care was measured using an assessment tool. Difference-in-difference analyses based on multiple linear regressions were used to compare the changes over time, after controlling for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 17 publications
3
41
1
1
Order By: Relevance
“…We employed difference‐in‐differences analyses to control baseline data and any potential confounding factors. Second, the study was conducted in two county hospitals in rural Guangxi, and its results should not be overextrapolated to other parts of China because areas differ considerably as to their implementation of national policies . Third, the study was conducted in county hospitals, and the results may not apply to general practitioners in township and village clinics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We employed difference‐in‐differences analyses to control baseline data and any potential confounding factors. Second, the study was conducted in two county hospitals in rural Guangxi, and its results should not be overextrapolated to other parts of China because areas differ considerably as to their implementation of national policies . Third, the study was conducted in county hospitals, and the results may not apply to general practitioners in township and village clinics.…”
Section: Discussionmentioning
confidence: 99%
“…All data were analysed using Stata 13.1 (StataCorp LP, College Station, TX, USA). We employed difference‐in‐differences analysis to explore the potential policy effect on antibiotics prescribing at the individual level over the two time periods (2011 vs . 2014), after adjusting potential confounding variables including patients’ age, gender, whether the prescription was issued on a weekday or not and secondary diagnosis of lower respiratory tract infections for inpatient records.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research showed that the more times a patient visits a basic-level health organization, the higher PCAT score that he/she would report [41]. This may be due to the fact that chronic condition management and health care for senior citizen are included in the basic public health service package, and the policy of implementing equalized public health services allowed these groups access to better primary care.…”
Section: Discussionmentioning
confidence: 99%
“…It reported that quality scores improved in Shanghai, where specific policies regarding clinical and preventive care were implemented in CHCs to promote general practitioner team service, while quality of care declined in Shenzhen, where CHCs were more profit-driven. [26] Studies in China also showed that government owned CHCs provided higher quality of care, and reported higher blood pressure control rates among hypertensive patients managed in CHCs when compared with hospital-owned or private-owned CHCs. [18,27,28] …”
Section: Discussionmentioning
confidence: 99%